Manajemen Kurikulum pesantren Muaddalah dalam Peningkatan kompetensi santri di Pesantren Tarbiyatunnasyiin Paculgowang Jombang - Muhammad zahdi husaini Zahdi; Nur 'Azah (Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
In the era of globalization and technological progress,the challenges faced by santri are not only limited to understanding religion, but also involve skills and knowledge in other fields that can make them better prepared to face the dynamics of modern society. This research aims to reveal how the planning, implementation and evaluation of the Mujadi Islamic Boarding School curriculum at the Tarbiyatunnasyiin Pacul Gowang Jombang Islamic Boarding School plays a role in improving the competency of students. This research uses a qualitative approach with descriptive methods. Data was obtained through interviews, observation and documentation studies. The main instrument is the researcher himself, with the help of interview and observation guidelines. The research was conducted at the Tarbiyatunnasyiin Pacul Gowang Islamic Boarding School and will last for a maximum of 3 months. Data analysis was carried out interactively using the Milles Matthew B, A. Michael Huberman, and Johnny Saldana methods. The validity of the data is checked through triangulation, detailed description, audit tracing, and confirmation audit tracing. The results of this research show that the Tarbiyatunnasyiin Islamic Boarding School has an established and consistent curriculum with a lawful approach, using the yellow book as the main guide. The planning process involves decision making by stakeholders to achieve learning objectives. The curriculum aims to develop the knowledge, character and skills of students through learning programs and extracurricular activities. Learning evaluation is carried out periodically through mid- and end-of-semester evaluations, homeroom teacher evaluations, and institutional evaluations every three months. The participation of teachers and homeroom teachers in evaluations reflects a commitment to improving the quality of education. This Islamic boarding school is committed to increasing the intelligence of students in cognitive, affective and psychomotor aspects through holistic learning.Keywords: Curriculum Management, Mujadi, Islamic Boarding School.